Women Cultural Role During the Umayyad Period in Bilad Al- Sham - Al Harthy, Noura Ahmed Hamed (Journal of Humanities & Social Sciences, 2018)
The rise of the Umayyad Caliphate in Bilad al- Sham opened new horizons in the issues of social, political and religious life's. The new Islamic society had different groups of people; the Mawali, Byzantines and Persians. The New political conditions formed many groups, parties, doctrines and different attitudes. New religious currents have emerged, for instance asceticism and mysticism. The Umayyad Women had interacted with all those variables. She covered all fields of the religious sciences, as well as she Introduced the basics of asceticism and mysticism in the religious and cultural behavior.On the literary side, the Umayyad women wrote in all literature categories. Her creativity had appeared in the art of music, singing, lyric. The presence of women in applied science is less than previous fields. Some of them had worked in medicine, chemistry and astronomy.The Umayyad community was expanded to all through the space of freedom that paved the way for prosperity of the lives of women religious, cultural, literary and scientific in the Levant Umayyad community was expanded to all through the space of freedom that paved the way for prosperity of the lives of women religious, cultural, literary and scientific in the Levant.
Keywords: women; Umayyad; Levant; cultural; scientific; institutions